1994
DOI: 10.1007/bf02347239
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary study of nectar production of the field cress, Rorippa indica, in relation to the age of its flowers

Abstract: Floral nectar production quantity and changes in sugar concentration of the nectar of Rorippa indica were investigated. Flowers were sorted by age. The small flower size was a major factor for the use of BCG test paper in nectar sampling. In flowers of the youngest age category, the nectar volume increased toward the night and decreased during the day. The amount of sugar in the nectar decreased with flower age. The sugar concentration was lower at night than daytime. The variability and changes in nectar conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 10 publications
1
0
0
Order By: Relevance
“…The nectar production pattern is similar to that observed in other studies (e.g . Feinsinger 1978;Muraoka & Watanabe 1994). These have suggested that a higher production during male phase would increase pollen export (Mitchell 1993).…”
Section: Discussionsupporting
confidence: 88%
“…The nectar production pattern is similar to that observed in other studies (e.g . Feinsinger 1978;Muraoka & Watanabe 1994). These have suggested that a higher production during male phase would increase pollen export (Mitchell 1993).…”
Section: Discussionsupporting
confidence: 88%